Profitability Analysis In Measuring Financial Performance at PT. Waskita Karya (Persero) Tbk on Indonesia Stock Exchange - Nahdiah Rezki Kamal; M. Ikhwan Maulana; Anwar Rauf (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
Companies must observe and analyze the company's performance in order to survive, one of which is to conduct a performance analysis from the financial side of the financial statements. This study aims to determine the financial performance of PT. Waskita Karya (Persero) Tbk for six years (2015-2020) based on profitability analysis. This type of research is quantitative descriptive. The population in this study is the financial statement data of PT. Waskita Karya (Persero) Tbk for the period 2015-2020, while the sample in this study is financial statements consisting of balance sheet, income statement, and cash flow statement of PT. Waskita Karya (Persero) Tbk for the period 2015-2020. Data collection techniques are carried out with documentation techniques. The results showed that the ability of PT. Waskita Karya (Persero) Tbk from profitability, namely in obtaining profits, generating profits using total assets, and the ability to generate profits using good equity in four years, namely 2015-2018 but in 2019-2020 it was not good and was unable to maximize returns. Profit and meet the interests of the company and shareholders. Overall, it can be said that the performance of PT. Waskita Karya (Persero) Tbk, was quite good in 2015-2018 and not good in 2019-2020 because its performance was still below industry standards.